La Guerra Civil en Castilla-La Mancha : de El Alcázar a Los Llanos / Manuel Ortiz Heras (coordinador); prólogo de Josep Fontana - Ortiz Heras, ManuelFontana, Josep (1931-) (Biblioteca aįl ; 9)
Bibliografía p. 295-304